KECENDERUNGAN POLA PERILAKU AGRESIF DAN EKSPLOSIF REMAJA (STUDY KASUS PERILAKU DELINKUENSI PELAJAR DI YOGYAKARTA, PERSPEKTIF SOSIO-RELIGIUS-EDUKATIF) - Subiyantoro Subiyantoro; Nurrohmah Nurrohmah (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2020)
This study aims to determine the tendency of aggressive and explosive behavior of adolescents (student delinquency actors) in the Yogyakarta area, which in this case the researchers conducted research at the Sleman Police, Class 1 Child Correctional Center (BAPAS), and the Youth Social Protection and Rehabilitation Center (BPRSR). ) Yogyakarta in Sleman. This qualitative research in collecting data using in-depth interviews / in-dept interviews, observation/observation, and documentation. The data analysis applies Miles and Huberman's theory, with the following steps: data reduction, data display, verification. The results showed that the tendency of adolescent aggressive and explosive behavior had elements of revenge and trial and error. The factors causing aggressive and explosive behavior are caused by the underdevelopment of adolescents regarding the development of social cognition, the development of moral reasoning, and the development of a lack of understanding of religion. Besides that, family attention that is not optimal and the negative influence of